Gestión Técnica de los Factores de Riesgo Ergonómico Para el Proceso de Producción de Asfalto Perteneciente al Gobierno Autónomo Descentralizado Provincial de Bolívar. - Llumiguano Llumiguano, Danny Alexis (2022)
Occupational health and safety are considered as one of the most important aspects for the productive development of companies, since this not only leads to minimize or control the different risk factors, but also contributes to the development in terms of productivity. The objective of this research was to carry out a technical management of ergonomic risk factors for the asphalt area, for which a descriptive type of research was used, from a nonexperimental design and a qualitative approach. The technique used were surveys, direct observation and ergonomic analysis methods already established such as: Rula, Reba, Owas, Ocra and JSI for the evaluation of risk factors. The population consisted of a total of 16 employees, distributed in 11 workstations. According to the deduction of the research work, the existence of two ergonomic risk factors was determined, such as: forced postures, identified in 11 workstations and repetitive movements, identified in 8 workstations. The activities with the highest exposure to these factors are: Front aggregate distributor assistant, rear aggregate assistant and shoveler or rake, since, they are exposed to a high risk level and improvement actions should be taken in relation to the two factors. The other positions are exposed to a medium and low risk level, therefore, a proposal was established, which consists of an ergonomic risk prevention plan, in order to contribute to the improvement of the work environment.